Peningkatan Hasil Belajar IPA Pada Materi Perubahan Energi Listrik Dengan Menggunakan Media Power Point Di Kelas VI SD Negeri 2 Rumbuk Timur Tahun Pelajaran 2020/2021 - Sabariah (Lembaga Bale Literasi, 2022)
The type of research used is Classroom Action Research (CAR). The purpose of this classroom action research (CAR) is to find out how far science students' learning outcomes are increased by applying the use of Power Point Media. In class action research (PTK) this was carried out in 2 cycles, from the results of the actions taken it was proven to be able to improve student learning outcomes by achieving the specified classical completeness of 85%. Classical Completeness 70% obtained in cycle I, can be increased in cycle II to 100%. In terms of student activity there was also an increase, namely in cycle I, the moderately active category was obtained, increasing to the active category. The results of this action research indicate that the application of the use of Power Point Media can improve student learning outcomes in science lessons with completeness reaching 100%.